An Adult Case of Asymptomatic Congenital Tracheal Stenosis - Saijo, Shigeru; Shiga, Kiyoto; Tateda, Masaru; Yokoyama, Jyunkichi (Nippon Jibi Inkoka Gakkai Kaiho, 1999)
We report an adult case of asymptomatic congenital tracheal stenosis. A 42-year-old woman was admitted to our hospital, whose chief complaint was tongue pain. Clinical examination revealed a tumor 35×20mm in diameter along the middle, right edge of the tongue, and histopathological examination determined a diagnosis of squamous cell carcinoma of the tongue. She had no history of dyspnea, stridor nor recurrent pneumonia, and enjoyed playing table tennis in her daily life. Physical examination, electrocardiogram, spirogram and laboratory data showed no abnormal signs although chest roentgenogram revealed a narrowed trachea 6mm in diameter, however, the tracheal stenosis was not noted at the time. On the 10th hospital day, radical operation for cancer of the tongue including right hemiglossectomy and supraomohyoid neck dissection, were performed. Oral intubation was not successful, and a tracheostomy was conducted. The trachea was incised, and revealed that complete tracheal rings existed without posterior membraneous tissue. The operation time was limited because of high airway pressure for a narrow tracheal tube (5mm in diameter). The main postoperative complication was one crust formation in the tracheal lumen that resulted in CO2 narcosis due to check valve obstruction of the trachea on the 4th postoperative day. A nebulizer provided continuous moisture and was effective in preventing recurrence of the crust attachment to the tracheal membrane, thus, the tracheostoma was closed by the 17th postoperative day. This case indicates that among healthy people there are extremely rare patients with congenital tracheal stenosis who survive their postnatal and infantile periods, and who experience no trouble in their daily lives. As physicians, we must be aware of this disease in adult patients in our clinics.